Demonstration of feasible waste plastic pyrolysis through decentralized biomass heating business model. (10th August 2022) - Byun, Manhee; Dickson, Rofice; Brigljević, Boris; Lee, Boreum; Lim, Dongjun; Upadhyay, Mukesh; Sargunan S Paramanatham, Salai; Nagulapati, Vijay Mohan; Haider, Junaid; Lim, Hankwon
Abstract: As the global recycling industry has collapsed since the China import ban of 2017, the amount of plastic waste has been rapidly increasing with little to no economic incentives for its utilization as a feedstock. For the first time, this work demonstrates a proof of concept, pilot-scale cogeneration system for biomass heating and plastic-derived pyrolytic oil production (MacroConverter ®). Furthermore, a disruptive techno-economic business model for decentralized plastic pyrolysis is assessed and compared with a traditional centralized industrial system through superstructure supply-chain optimization. Results of this initial assessment indicate that using a decentralized plastic pyrolysis model, combined with seasonal heating demand, profitability can be increased (1.3–2.4 x) and the process is unlikely to show a loss of profit whereas the centralized process may show losses. Furthermore, compared to centralized pyrolysis, transportation costs, and related CO2 emissions were significantly decreased by 3–10 x and 1.4–7 x respectively. Highlights: Pilot process for plastic pyrolysis-biomass heating cogeneration is demonstrated. Decentralized plastic pyrolysis business model is developed and assessed. Quantitative comparison of centralized and decentralized systems. Superstructure supply-chain optimization. Significant economic and environmental benefits are demonstrated.